Utilising Fibre Reinforced Polymer (FRP) to Enhance the Flexural Capacity of Concrete Structures After Earthquakes - Garup Lambang Goro; Nor Puji Lestari; Primasiwi Harprastanti; Aiun Hayatu Rabinah; Jamal Mahbub; Stefanus Santosa; Adibtyas Samudera Putra Larosa; Aviolita Sekar Nanda Kurniawan (International Journal of Integrated Engineering, 2025)
Increasing the bending capacity of post-earthquake concrete structures is crucial for ensuring the safety and sustainability of buildings. This study evaluates the effectiveness of using Carbon Fibre Reinforced Polymer (CFRP) materials as a reinforcement solution to enhance the bending capacity of concrete structures damaged by earthquakes. CFRP was selected due to its advantageous characteristics, including high strength, corrosion resistance, and ease of application in the field. The study employs an experimental approach, utilising concrete beams with varying reductions in strength to simulate damage levels of 65%, 50%, and 30%. The tests conducted include density, compressive strength, and flexural strength assessments. The results indicate that the application of CFRP significantly increases the flexural capacity of concrete beams, reduces crack formation, and extends the service life of the structures. Specifically, the flexural strength improves 3 to 4 times for unreinforced and reinforced concrete beams. These findings confirm that CFRP is an effective and efficient solution for the rehabilitation of post-earthquake concrete structures, contributing positively to infrastructure recovery in earthquake-prone areas.